Facile synthesis of Pt-Cu@silicon nanostructure as a new electrocatalyst supported matrix, electrochemical detection of hydrazine and hydrogen peroxide. (1st February 2016) - Ensafi, Ali A.; Abarghoui, Mehdi Mokhtari; Rezaei, Behzad
Highlights: A facile approach is presented to synthesis Pt-Cu nanoalloy. Pt-Cu nanoalloy was supported on the surface of porous silicon using in-situ redox reaction. The morphological and electrochemical properties of the nanostructure were characterized. Pt-Cu@PSi was successfully used toward hydrazine oxidation and H2 O2 reduction. The prepared sensor was used to determine H2 O2 and hydrazine in real samples. Abstract: In this work, a facile approach is presented to synthesis Pt-Cu nanoalloy with time scale of a few minutes at room temperature. Pt-Cu nanoalloy was supported on the surface of porous silicon (PSi) powder by a simple in-situ redox reaction between PtCl6 2− /Cu 2+ and PSi, in hydrofluoric acid solution. The morphological, chemical and electrochemical properties of the prepared nanostructure were characterized using field emission scanning electron microscopy, X-ray diffraction spectroscopy, energy dispersive X-ray spectroscopy, cyclic voltammetry and chronoamperometry. Then, the electrocatalytic activity of Pt-Cu@PSi toward hydrazine oxidation and hydrogen peroxide reduction was investigated and were compared with Pt@PSi and Cu@PSi. The results showed that Pt-Cu@PSi has higher electrocatalytic for both the analytes. To have better behavior of the electrocatalyst for the detection of hydrazine and hydrogen peroxide, Pt-Cu@PSi modified carbon ionic liquid electrode (CILE) was fabricated. Using the proposed electrochemical sensor, hydrogen peroxide could be measured in the range of 0.5–1280 μmol L −1 with detection limit of 100 nmol L −1, whereas hydrazine could be measured in the range of 0.20–1680 μmol L −1 with detection limit of 50 nmol L −1, using chronoamperometry technique. Finally, the prepared electrochemical sensor was employed to determine hydrogen peroxide and hydrazine in real samples with satisfactory results.